Effect of blood activity on dosimetric calculations for radiopharmaceuticals. (14th October 2016) - Zvereva, Alexandra; Petoussi-Henss, Nina; Li, Wei Bo; Schlattl, Helmut; Oeh, Uwe; Zankl, Maria; Graner, Frank Philipp; Hoeschen, Christoph; Nekolla, Stephan G; Parodi, Katia; Schwaiger, Markus
Abstract: The objective of this work was to investigate the influence of the definition of blood as a distinct source on organ doses, associated with the administration of a novel radiopharmaceutical for positron emission tomography-computed tomography (PET/CT) imaging—(S)-4-(3- 18 F-fluoropropyl)-L-glutamic acid ( 18 F-FSPG). Personalised pharmacokinetic models were constructed based on clinical PET/CT images from five healthy volunteers and blood samples from four of them. Following an identifiability analysis of the developed compartmental models, person-specific model parameters were estimated using the commercial program SAAM II. Organ doses were calculated in accordance to the formalism promulgated by the Committee on Medical Internal Radiation Dose (MIRD) and the International Commission on Radiological Protection (ICRP) using specific absorbed fractions for photons and electrons previously derived for the ICRP reference adult computational voxel phantoms. Organ doses for two concepts were compared: source organ activities in organs parenchyma with blood as a separate source (concept-1); aggregate activities in perfused source organs without blood as a distinct source (concept-2). Aggregate activities comprise the activities of organs parenchyma and the activity in the regional blood volumes (RBV). Concept-1 resulted in notably higher absorbed doses for most organs, especially non-source organs with substantial blood contents, e.g. lungs (92% maximum difference). Consequently, effective doses increased in concept-1 compared to concept-2 by 3–10%. Not considering the blood as a distinct source region leads to an underestimation of the organ absorbed doses and effective doses. The pronounced influence of the blood even for a radiopharmaceutical with a rapid clearance from the blood, such as 18 F-FSPG, suggests that blood should be introduced as a separate compartment in most compartmental pharmacokinetic models and blood should be considered as a distinct source in dosimetric calculations. Hence, blood samples should be included in all pharmacokinetic and dosimetric studies for new tracers if possible.